PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT GRAHA ANUGERAH KEDIRI DI KOTA BATAM - zhou, davidzhou; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2025)
This study examines how work motivation, work discipline, and job satisfaction influence employee performance individually and collectively at PT Graha Anugerah Kediri in Batam City. Responding to organizational needs for sustained performance improvement, we conducted a quantitative survey of 119 employees using a structured questionnaire. Data were analyzed with SPSS version 27 through descriptive statistics, validity and reliability testing, classical assumption checks, and multiple regression to estimate partial and simultaneous effects. Findings indicate that work motivation, work discipline, and job satisfaction each exert a positive and statistically significant influence on employee performance, with motivation and discipline emerging as the strongest predictors; together, the three variables explain a substantial proportion of performance variance. These results suggest that integrated human resource management strategies that foster motivational drivers, reinforce consistent discipline, and enhance employee satisfaction can meaningfully improve workforce outcomes at PT Graha Anugerah Kediri and similar organizations.